Renal metastasis of esophageal squamous cell carcinoma coexisting with adenoid cystic carcinoma: a case report and literature review - Wu, An-Qi; Bao, Qiu-Hong; Pang, Jian-Ming; Chen, Qing-Qing (Frontiers in Oncology, 2026)
Esophageal cancer is one of the common malignancies worldwide. It frequently metastasizes to the lungs and liver, as well as to distant sites such as bones, heart, and brain. Clinically, renal metastasis is rare, but it is more frequently observed in autopsy specimens. The present case report describes a rare case of renal metastasis from esophageal squamous cell carcinoma coexisting with adenoid cystic carcinoma.